Relações entre a disseminação do SARS-COV-2 e o saneamento básico inadequado - Reges, Layla Bruna Lopes (Universidade Federal Rural do Semi-Árido, 2021)
Basic sanitation is a set of services that constitute the structure of development at global, national and local levels, since it covers the social, environmental and economic spheres and reveals that its absence or inadequacy results in impacts that affect the health of the population, the economy and the environment. The present work aims to study the relationship between the spread of SARS-CoV-2 and the inadequacy of basic sanitation intermediating impacts that cover several areas. In order to gather data and information on the subject, a bibliographic research was carried out about specific themes such as: the importance of the functions and services offered by basic sanitation; the situation of sanitation in the context of ancient and current times; the characterization and forms of transmission of SARS-CoV-2; the importance of basic sanitation; the presence of SARS-CoV-2 in solid waste and in the environment; the social, environmental, and economic impacts generated by the inadequacy of sanitation services, as well as their relation to the spread of the COVID-19 virus; as well as the mitigating measures related to the impacts and the spread of SARS-CoV-2. The information collected demonstrated the importance of sanitation in preventing disease and promoting quality of life, besides the fact that its absence or inadequacy and, consequently, the spread of the virus can generate health impacts (infections in the intestinal and respiratory tracts); impacts on the economy (with the isolation and confinement of the labor market and cargo transportation, as well as in the treatment of diseases related to inadequate sanitation), and on the environment (with the contamination of surface and ground waters and environmental degradation with the increase of solid medical waste with inadequate disposal). With this, necessary measures to be applied were pointed out with the purpose of seeking to mitigate the problems involving the inadequacy of sanitation
Keywords: Pandemia; Esgotamento sanitário; Resíduos sólidos; Meio ambiente; Impactos; Saúde pública; Covid-19; Sewage; Solid waste; Environment; Impacts; Public health; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA